Novice Teacher’s Needs in Starting Career as an Educator - Mohd Isha Awang; Abdull Sukor Shaari (Universitas Muhammadiyah Sidoarjo, 2021)
A new teacher is an individual who has just started a career in the field of teaching with less than three years of experience. They need certain aspects as a new teacher in starting a career as a teacher. This requirement is an important aspect that will contribute to the effectiveness of their teaching in the classroom. A study aimed at identifying the needs of new teachers starting this career using a survey research design. The questionnaire was used as a research instrument to review a simple randomly selected study sample involving 177 new teachers. The study found several aspects that are necessary for new teachers such as mentoring aspects, school support, key information, teaching and learning practices and co-curricular activities. This study has important implications to the school, State Educational Department and Ministry of Education in providing ongoing support to new teachers and then to develop their level of professionalism in the classroom in particular and in the education profession in general.